2013
DOI: 10.3346/jkms.2013.28.9.1399
|View full text |Cite
|
Sign up to set email alerts
|

Muscular Sarcoidosis Detected by F-18 FDG PET/CT in a Hypercalcemic Patient

Abstract: Sarcoidosis is a systemic granulomatous disease of unknown etiology that involves many organs, occasionally mimicking malignancy. We herein report a 50-yr-old woman of muscular sarcoidosis of chronic myopathic type, manifested by hypercalcemia and muscle wasting. Besides insignificant hilar lymphadenopathy, her sarcoidosis was confined to generalized atrophic muscles and therefore, F-18 FDG PET/CT alone among conventional imaging studies provided diagnostic clues for the non-parathyroid-related hypercalcemia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Moreover, 18 F-FDG PET has been proven to be a very useful imaging technique in diagnosis, disease activity assessment, monitoring treatment response, and risk assessment in patients with sarcoidosis [ 10 ]. In suspected or known sarcoidosis patients, PET-CT may be useful in the evaluation of disease extent and monitoring treatment response [ 11 ]. In atypical, complex, and multisystem sarcoidosis, PET-CT plays an important role for the evaluation of the localization and effect of treatment [ 12 ].…”
Section: Case Presentationmentioning
confidence: 99%
“…Moreover, 18 F-FDG PET has been proven to be a very useful imaging technique in diagnosis, disease activity assessment, monitoring treatment response, and risk assessment in patients with sarcoidosis [ 10 ]. In suspected or known sarcoidosis patients, PET-CT may be useful in the evaluation of disease extent and monitoring treatment response [ 11 ]. In atypical, complex, and multisystem sarcoidosis, PET-CT plays an important role for the evaluation of the localization and effect of treatment [ 12 ].…”
Section: Case Presentationmentioning
confidence: 99%
“…Three clinical subtypes of muscular sarcoidosis are known: chronic myopathy, acute myositis, and nodular myositis 9 . Chronic myopathy is the most common form, followed by proximal symmetric muscle weakness/atrophy with normal or elevated serum levels of muscle enzymes 8 . This pattern is unfortunately related with thoracic involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Radiologic procedures are also unable to discriminate active disease. It is suggested that hybrid imaging methods may be helpful in evaluation of granulomatous diseases 8,21 …”
Section: Discussionmentioning
confidence: 99%
“…The potential use of FDG PET/CT in diagnostic evaluation and monitoring treatment response in granulomatous myositis secondary to sarcoidosis has already been reported in few case studies in the past. [ 9 10 11 ] PET/CT can also help in guiding biopsy from the most accessible site which is showing high degree of FDG uptake. Diffuse FDG in the skeletal muscles is, however, not a specific finding for granulomatous myositis; it can also be seen in the patients with dermatomyositis/polymyositis, thyrotoxicosis, and in patients where PET/CT scans was done in fed state or hyperinsulinemia.…”
Section: Discussionmentioning
confidence: 99%